2022
DOI: 10.1037/trm0000326
|View full text |Cite
|
Sign up to set email alerts
|

Making meaning of disaster experience in highly trauma-exposed survivors of the Oklahoma City bombing.

Abstract: Survivors of disasters can be expected to form meaningful perspectives on their experiences that shape their trajectories of recovery; thus, these perspectives are important to study. If humans are naturally compelled to create meaning from traumatic experiences, the creation of meaning should be evident in survivors' discussion of the effects of the disaster in their lives. Therefore, the purpose of this study of highly trauma-exposed disaster survivors was to identify meaningful aspects or outcomes of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The collection of the current study’s long-term data elicited from survivor stories collected decades after the event has provided new insights into the later stages of thoughts and feelings, coping, and processing of the event not provided by previous shorter-term findings. These long-term data have confirmed that many of the early thoughts and emotions and perspectives (Abu-Hamad et al, 2022; Lee et al, 2021; Turner et al, 2022) have persisted, although some have diminished. The long-term qualitative data further revealed later directions in the survivors’ lives in the development of these processes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The collection of the current study’s long-term data elicited from survivor stories collected decades after the event has provided new insights into the later stages of thoughts and feelings, coping, and processing of the event not provided by previous shorter-term findings. These long-term data have confirmed that many of the early thoughts and emotions and perspectives (Abu-Hamad et al, 2022; Lee et al, 2021; Turner et al, 2022) have persisted, although some have diminished. The long-term qualitative data further revealed later directions in the survivors’ lives in the development of these processes.…”
Section: Discussionmentioning
confidence: 67%
“…Less research has been conducted specifically on terrorism, and almost all of the research has examined general populations (e.g., Chen et al, 2003;Fredrickson et al, 2003;Schuster et al, 2001;Silver et al, 2002) with few focusing on directly exposed survivors. Some studies of feelings, coping, and cognitive and emotional processing of the experience among directly exposed survivors of terrorist attacks have been conducted in the first few months and years after the incident, finding both positive (e.g., gratitude, happiness, and peacefulness) and negative (e.g., fear, sadness, and anger) emotions, various coping methods, and cognitive processing of the event (e.g., Abu-Hamad et al, 2022;Fredrickson et al, 2003;Lee et al, 2021;North et al, 2015North et al, , 1999North et al, , 2005aNorth et al, , 2005bNorth et al, , 2001Pérez-Sales et al, 2005;Shaw et al, 2021;Tran & North, 2017;Turner et al, 2022;Vázquez et al, 2005;Weinberg et al, 2014). Research studies have underutilized qualitative methods to investigate the outcomes of terrorist incidents.…”
mentioning
confidence: 99%
“…The authors of the current article have previously theorized that there is a natural drive to make meaning of exposure to disaster (Lee et al 2022). It is apparent from this study's findings that one's reactions and feelings are part of this meaning-making process.…”
Section: Discussionmentioning
confidence: 76%
“…These questions, listed in Table 1, are the source of data for this analysis. Participants' answers to these interview questions were manually recorded immediately in writing by the interviewer and typed into a research document providing separate responses to each of these questions for each participant, a procedure successfully used in other disaster research by this team (Dang et al 2022;Lee et al 2022;Miu et al 2022;Shaw et al 2021;Tran and North 2017). Because the interviews were not audio recorded for transcription, the illustrative quotes represent the interviewers' paraphrasing and not necessarily exact wordfor-word transcription of the participants' responses.…”
Section: Methodsmentioning
confidence: 99%
“…While the pandemic exacerbated states of existential distress (Upenieks 2022) and vaccine skepticism motivated by religious reasons (Zarzeczna et al 2023), spirituality proved useful in counteracting emotions of fear, anxiety, loss of hope (Buchtova et al 2022), depressive symptoms (de Souza et al 2023) and stress (Kosic et al 2023), in grieving the loss of a family member (Biancalani et al 2022) or in fostering individual practices such as praying at home (Apergis et al 2023), with consequences differentiated according to a wide variety of factors such as age (Keisari et al 2022), socioeconomic status (Safdar et al 2023) or health status (Durmuş and Durar 2022). But survivors of such crisis situations and dramatic episodes may activate sensemaking processes that involve a revision of one's value orientation, stimulating innovative spiritual reflection on life and death, the effect of which is a change, even a profound one, in personal priorities and aspirations (Lee et al 2022). Some research on war veterans, for example, indicates that battlefield experience may be a trigger factor that prompts the acquisition of a previously unexpressed spirituality in military personnel, giving scientific grounding to the popular adage "there are no atheists in foxholes" (Snape 2015).…”
Section: Introductionmentioning
confidence: 99%